Pengaruh Earning Per Share (EPS), Price To Book Value (PBV), Dan Debt To Equity Ratio (DER) Terhadap Harga Saham Pada PT Lippo Karawaci Tbk Periode 2015-2024 - Latifa Tri Salma; Vidya Amalia Rismanty (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to examine the effect of Earnings Per Share (EPS), Price to Book Value (PBV), and Debt to Equity Ratio (DER) on stock prices at PT Lippo Karawaci Tbk during the 2014–2025 period. The independent variables used in this study are Earnings Per Share, Price to Book Value, and Debt to Equity Ratio, while the dependent variable is stock price. This study employs a quantitative descriptive approach, with the population consisting of the financial position reports of PT Lippo Karawaci Tbk. Data were collected using the documentation method and literature review. The analytical methods used include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, coefficient of determination (R²), t-test, and F-test with a significance level of 0.05, processed using IBM SPSS Statistics version 26. The results of the hypothesis testing show that the calculated F-value is greater than the F-table value (9.173 > 4.76), which is further supported by a p-value < 0.05 (0.012 < 0.05). Therefore, H₀ is rejected and Ha is accepted, indicating that Earnings Per Share, Price to Book Value, and Debt to Equity Ratio simultaneously have a significant effect on stock prices at PT Lippo Karawaci Tbk during the 2015–2024 period.